The diagnostic performance of cardiac magnetic resonance in detection of myocardial involvement in AL amyloidosis. (13th November 2014) - Fikrle, Michal; Palecek, Tomas; Masek, Martin; Kuchynka, Petr; Straub, Jan; Spicka, Ivan; Rysava, Romana; Linhart, Ales
Summary: Background: The non‐invasive assessment of amyloid heart disease may be challenging. Cardiac magnetic resonance (CMR) represents a method of choice for assessment of left ventricular (LV) morphology and function, and it also provides a unique possibility to evaluate the presence of amyloid deposition by the late gadolinium enhancement (LGE) technique. However, so far, published studies have not been consistent in terms of described LGE patterns associated with amyloid cardiomyopathy. Aims: To compare echocardiographic and CMR assessment of LV morphology and function and to evaluate the presence and pattern of LGE in a population of patients with AL amyloid cardiomyopathy. Methods: Twenty‐two consecutive patients with newly diagnosed AL amyloid cardiomyopathy and without contraindications to CMR were comprehensively examined by echocardiography and CMR. Results: Echocardiography and CMR did not differ in the evaluation of interventricular septal thickness, LV end‐diastolic diameter and ejection fraction. Significant differences were found between echocardiographic and CMR estimates of LV end‐diastolic volume ( P <0·01) and LV mass ( P <0·001). Various global LGE patterns (transmural homogenous or heterogeneous, subendocardial) were present in 17 patients (77%), patchy LGE was observed in one case (4·5%) and suboptimal nulling of the myocardium was reported in two subjects (9%). Conclusions: Echocardiography significantly overestimates LV mass and underestimates LV volumes in patients with AL amyloid cardiomyopathy as compared to CMR. As it is present in more than three quarters of individuals with AL amyloid cardiomyopathy, any type of global LGE pattern may be considered as pathogenomic for amyloid heart disease.